Early diagenesis in anoxic sediments of the Gulf of Gdańsk (southern Baltic Sea): Implications for porewater chemistry and benthic flux of carbonate alkalinity - Łukawska-Matuszewska, Katarzyna; Dwornik, Maciej (Frontiers in Earth Science, 2025)
Being a measure of acid-neutralizing capacity, alkalinity determines carbon dioxide (CO2) uptake from the atmosphere and the pH of seawater. However, the alkalinity budget in the Baltic Sea is still poorly understood. According to recent modeling studies, anaerobic processes in sediments are an important internal source of alkalinity in the Baltic Sea. Nevertheless, determining the role of sediments in alkalinity enhancement is difficult due to the high variability of environmental conditions and, consequently, biogeochemical processes. Here, we describe the geochemistry of different types of anoxic sediments from the Gulf of Gdańsk: methanic, methanic with freshwater seepage, and methane-free, emphasizing dissolved inorganic carbon, methane, and sulfate. We estimate the benthic flux of carbonate alkalinity (JCA) and the sulfate reduction rate (SRR) due to the dissimilatory sulfate reduction (DSR) and anaerobic methane oxidation with sulfate (SO42−-AOM), the main alkalinity-producing processes. We show that the role of anaerobic sediments as a source of alkalinity can vary significantly, depending on the benthic conditions. The concentration and the release of carbonate alkalinity (CA) from sediments depend on the SRR, type of the process producing CA (DSR and SO42−-AOM), and the depth of sulfate–methane transition (SMT) in the sediment. The estimated SRR is ranging from 0.1 to 26 nmol cm−3 d−1. The range of JCA obtained in the present study varies from 1037 to 2084 μmol m−2 d−1. Assuming the complete oxidation of sulfide released from the sediment to the bottom water, the net flux of CA (J*CA) in the study area is 943–2064 μmol m−2 d−1, with the highest values for sediment dominated with SO42−-AOM with fresh groundwater seepage, shallow SMT, and high SRR in the subsurface sediment layer. Our results may be useful for further studies to determine the role of sediments as an internal source of alkalinity to help close the alkalinity budget in the Baltic Sea.